2) Resolva as inequações, sendo U=Q:
a) 7 (-1) <5 - 2x
b) 6x – 3 (4-2x)>0
e) 2 (x-3) + 3(x-1) = 36
Respostas
respondido por:
1
Explicação passo-a-passo:
a) 7 (-1) <5 - 2x
-7 < 5 - 2x
-7-5 < -2x
-12 < -2x
2x > 12
x > 12/2
x > 6
b) 6x – 3 (4-2x)>0
6x -12+6x > 0
12x > 12
x > 12/12
x > 1
e) 2 (x-3) + 3(x-1) = 36
2x -6 +3x -3 = 36
5x = 36-9
5x = 28
x = 28/5
mikaela6047:
me ajudaa em uma esquaçao alguemm
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás